Disease-related autoantibody profile in patients with systemic sclerosis. (3rd October 2017) - Liaskos, Christos; Marou, Emmanouela; Simopoulou, Theodora; Barmakoudi, Maria; Efthymiou, Georgios; Scheper, Thomas; Meyer, Wolfgang; Bogdanos, Dimitrios P.; Sakkas, Lazaros I.
Abstract: Background: Autoantibodies (autoAbs) help in diagnosis and predicting clinical phenotypes in systemic sclerosis (SSc). Aim of the study: To determine the clinical utility of 13 SSc-related autoAbs in SSc patients. Material and methods: A total of 131 consecutive patients with SSc (111 female, mean age 58.1 ± 14 years; 49 with diffused cutaneous SSc [dcSSc] and 82 with limited cutaneous SSc [lcSSc]) were analysed by a multiplex line immunoassay (Euroimmun) for autoantibodies (autoAbs) against 13 SSc-related antigens. A total of 22 patients with primary Raynaud phenomenon (RP), and 22 healthy controls were also analysed. Results: ANA by indirect immunofluorescence was present in 128 (97.7%) patients with SSc. Excluding anti-Ro52, 113 (89.3%) SSc patients were positive for at least one autoAb: anti-Topoisomerase I (anti-Topo) I abs in 54 (41.2%), anti-centromere proteins (anti-CENP) in 37 (28.2%, all reactive with centromere protein-A (CENPA) and centromere protein B (CENPB)), anti-RNA polymerase III(RP11) in 19 (14.5%), anti-RNA polymerase III(RP155) in 13 (9.9%), anti-fibrillarin in 4 (3.1%), anti-Ku in 6 (4.6%), anti-nucleolus-organizing region (anti-NOR90) in 8 (6.1%), anti-PM-Scl100 in 2 (1.5%), and anti-PM-Scl75 in 4 (3.1%). There was no immunoreactivity for Th/To or platelet-derived growth factor receptor (PDGFR). Overall, 102 (77.9%) SSc patients had autoAbs against Topo I, CENPA or CENPB, RP11 or RP155. Anti-Topo I abs were strongly associated with dcSSc, interstitial lung disease (ILD) ( p < .001), pulmonary hypertension (PH) ( p = .019) and ILD-PH ( p = .003). Anti-CENPB abs were associated with lcSSc, and negatively associated with ILD. Anti-RP11 and anti-NOR90 abs were associated with male gender, and anti-NOR90 associated with ILD. Conclusions: Anti-Topo I, anti-CENP, and anti-RNA pol III are the most prevalent autoAbs in SSc. Anti-Topo I and anti-NOR90 abs are associated with ILD and/or PAH.